Reorganization of agricultural production through FELCRA : participants’ perception towards group-farming programmes in Peninsular Malaysia. - Redzuan, Ma’rof; Aref, Fariborz (IDOSI Publications, 2009)
This study was designed to examine the nature of perception of the participants towards the programme with a view to determine to what extent the people understood and internalised all aspects of the programme and hence try to intelligently conjecture possible underlying reasons for any poor performance on part of the participants. Specifically, the study attempted to assess the participants’ response towards group farming as a concept and to identify factors related to their perception. Finally it is hoped that socio-economic implications thus derived would allow for some policy guidelines to be drawn. This is important in view of the possible impact of the reorganization of the production system had on the traditional smallholders; with the introduction of a more formally schemes structure management under the FELCRA authority.